Rozwiąż równanie.
a) x³-4x²+3x=0
b) x³+3x²+2x=0
c)x⁴=4x³+5x²
d)6x³+9x²=3x⁴
e) 2x⁵=2x⁴+12x³
f)10x⁴+x³=2x²
g)9x⁶+6x⁵+x⁴=0
h)x⁵+4x⁴=12x³
i) x³+4x=-5x²
j) -½ x ⁴+x³=½x²
k)18x⁵=x⁷+3x⁶
l) 16x⁶+8x⁴+x²=0
m)x³-3x²-4x+12=0
n)2x³+3=x²+6x
o)x³+5x²=3x+15
p)x⁴+9x³=x+9
r)1-x³=x²-x
s)x⁴-8x=8-x³


Duzo punktów wiec proszę o dobre odp.

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T16:13:12+01:00
Rozwiąż równanie.
a) x³-4x²+3x=0
x(x²-4x+3)=0
x(x-1)(x-3)=0
x=0∨x=1∨x=3

b) x³+3x²+2x=0
x(x²+3x+2)=0
x(x+1)(x+2)=0
x=0∨x=-1∨x=-2

c)x⁴=4x³+5x²
x²(x²-4x-5)=0
x²(x-5)(x+1)=0
x=0∨x=5∨x=-1

d)6x³+9x²=3x⁴
3x⁴-6x³-9x²=0
3x²(x²-2x-3)=0
3x²(x-3)(x+1)=0
x=0∨x=3∨x=-1

e) 2x⁵=2x⁴+12x³
2x⁵-2x⁴-12x³=0
2x³(x²-x-6)=0
2x³(x-3)(x+2)=0
x=0∨x=3∨x-2

f)10x⁴+x³=2x²
10x⁴+x³-2x²=0
x²(10x²+x-2)=0
x²(10x²+x-2)=0
Δ=81
√Δ=9
x=0∨x=-1/2 ∨ x=2/5

g)9x⁶+6x⁵+x⁴=0
x⁴(9x²+6x+1)=0
x⁴(3x+1)²=0
x=0∨x=-1/3

h)x⁵+4x⁴=12x³
x⁵+4x⁴-12x³=0
x³(x²+4x-12)=0
x³(x+6)(x-2))=0
x=0∨x=-6∨x=2

i) x³+4x=-5x²
x³+5x²+4x=0
x( x²+5x+4)=0
x( x²+5x+4)=0
Δ=9
√Δ=3
x=0∨x=-4∨x=-1

j) -½ x ⁴+x³=½x²
-½x²( x ²-2x+1)=0
-½x²( x -1)²=0
x=0∨x=1

k)18x⁵=x⁷+3x⁶
x⁷+3x⁶-18x⁵=0
x⁵(x²+3x-18)=0
x⁵(x+6)(x-3)=0
x=0∨x=-6∨x=3

l) 16x⁶+8x⁴+x²=0
x²(16x⁴+8x²+1)=0
x²(4x²+1)²=0
x=0

m)x³-3x²-4x+12=0
x²(x-3)-4(x-3)=0
(x²-4)(x-3)=0
x=2∨x=-2∨x=3

n)2x³+3=x²+6x
2x³-x²-6x+3=0
x²(2x-1)-3(2x-1)=0
(x²-3)(2x-1)=0
x=√3∨x=-√3∨x=1/2

o)x³+5x²=3x+15
x³+5x²-3x-15=0
x²(x+5)-3(x+5)=0
(x²-3)(x+5)=0
x=√3∨x=-√3∨x=-5

p)x⁴+9x³=x+9
x⁴+9x³-x-9=0
x³(x+9)-1(x+9)=0
(x³-1)(x+9)=0
x=1∨x=-9

r)1-x³=x²-x
x³+x²-x-1=0
x²(x+1)-1(x+1)=0
(x²-1)(x+1)=0
x=1∨x=-1

s)x⁴-8x=8-x³
x⁴+x³-8x-8=0
x³(x+1)-8(x+1)=0
(x³-8)(x+1)=0
x=2∨x=-1
ufff
1 5 1